2016
DOI: 10.1186/s12954-016-0094-1
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perceptions and operational barriers in the training and distribution of take-home naloxone within prisons in England

Abstract: BackgroundThe aim of the study was to assess potential barriers and challenges to the implementation of take-home naloxone (THN) across ten prisons in one region of England.MethodsQualitative interviews deploying a grounded theory approach were utilised over a 12- to 18-month period that included an on-going structured dialogue with strategic and operational prison staff from the ten prisons and other key stakeholders (n = 17). Prisoner perceptions were addressed through four purposive focus groups belonging t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
3
35
0
Order By: Relevance
“…Many participants referred either directly or indirectly to administering the whole naloxone dose at once which sparked a range of negative reactions from the recipient including acute withdrawal and aggressiveness. The potential for naloxone administration precipitating acute withdrawal has been noted in other studies (Neale and Strang, 2015;Worthington et al, 2006;Wright et al, 2006) and has been cited as a possible barrier to PWID using naloxone for peer administration (Sondhi et al, 2016;Sporer and Kral, 2007;Worthington et al, 2006;Wright et al, 2006). Although few participants in this study reported personal experiences of acute opiate withdrawal, their experiences of witnessing it in others to whom they had given naloxone were often distressing.…”
Section: Discussionmentioning
confidence: 51%
“…Many participants referred either directly or indirectly to administering the whole naloxone dose at once which sparked a range of negative reactions from the recipient including acute withdrawal and aggressiveness. The potential for naloxone administration precipitating acute withdrawal has been noted in other studies (Neale and Strang, 2015;Worthington et al, 2006;Wright et al, 2006) and has been cited as a possible barrier to PWID using naloxone for peer administration (Sondhi et al, 2016;Sporer and Kral, 2007;Worthington et al, 2006;Wright et al, 2006). Although few participants in this study reported personal experiences of acute opiate withdrawal, their experiences of witnessing it in others to whom they had given naloxone were often distressing.…”
Section: Discussionmentioning
confidence: 51%
“…The reasons "done with drugs" and "encourages abuse" arose in our study population, mirroring concerns elsewhere that THN kits with syringes could increase risky behavior or trigger opioid use relapses. [15][16][17] Nevertheless, THN program participation has been associated with decreased (rather than increased) high-risk opioid use. [29] Both patients accepting and refusing THN mentioned thoughts of suicide or not caring whether they overdosed.…”
Section: Discussionmentioning
confidence: 99%
“…In non-ED settings, factors contributing to refusals include reluctance to give injections, fear of triggering additional drug use, and inappropriate minimization of OD risk. [15][16][17][18][19] Conversely, patients are motivated to accept THN if they feel they can help others, [17,19,20] if they have had an OD themselves, [18] or if they know a peer with THN. [21] To improve quality and reach of ED THN distribution and education, it is crucial to gain greater understanding of reasons influencing THN refusal or acceptance in ED patients.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study focused on non-prisoners (Sondhi, Ryan, & Day, 2016). This study by Sondhi et al, also conducted across ten English prisons, employed qualitative interviews to assess the attitudes of prison-based healthcare staff and substance misuse service staff, along with naloxone suppliers and strategic leads for NHS England toward prison-based THN programs.…”
Section: ) Attitudes Of Non-prisoner Stakeholdersmentioning
confidence: 99%
“…Several of the recent studies within this review have begun shifting the focus of research toward aspects of program implementation and highlight gaps in this knowledge. Sondhi's evaluation of barriers to program implementation from the perspectives of prisoner and non-prisoner stakeholders has revealed a need to understand prison processes, explore implementation of training at different time points in an inmate's sentence, and engage prison staff of varying levels of seniority in order to address barriers to implementation such as identifying and recruiting eligible prisoners for training and disseminating THN kits (Sondhi et al, 2016;Sondhi, 2016). These variables may differ between settings and local assessment is likely to be required before design and implementation of a THN program.…”
Section: Addressing Technical Barriers To Implementationmentioning
confidence: 99%